Seasonal variation in yield and yield contributing characters of selected cocoa clones - Minimol, J. S.; Shija, T. K.; Suma, B.; Chithira, P. G.; Shilpa, K. S. (Journal of Plantation Crops, 2020)
Cocoa, the only source of chocolate, is divided into three groups viz. Forastero, Criollo and Trinitario. This study was taken up to gauge the performance of 12 years old cocoa clones of three types. Among these, Forastero was found to perform well under tropical conditions in all three seasons. The performance of Forastero was unrivaled with pod weight 429.95 g and wet bean weight 117.79 g. All three varieties performed well under post-monsoon season exploiting advantages of monsoon. When correlated with weather, it was observed that number of rainy days, rainfall and relative humidity had a negative correlation with number of pods, whereas mean sunshine hours had a positive correlation with pod weight, wet bean weight, and TSS. In order to comprehend the significance of weather parameters, canonical correlation was estimated. The high value indicated that all the weather parameters influenced the characters to a great extent. Rainfall, temperature and relative humidity were the three climatic factors influencing the yield parameters. High R2 value obtained in prediction model suggested that it could be efficiently used in the prediction of yield and yield contributing characters of cocoa.